Development and optimisation of extruded bio-based polymers from poultry feathers. (5th September 2021) - McGauran, Thomas; Harris, Matt; Dunne, Nicholas; Smyth, Beatrice M.; Cunningham, Eoin
Graphical abstract: Highlights: Poultry feather powder (and plasticiser) extruded into a continuous polymer filament. Shearing force, pressure, temperature required for stable feather polymer formation. No major changes incurred after reprocessing, suggesting potential to be reprocessed. Parameters impacting mechanical and processing properties determined. Feather based polymers significantly cheaper than common commodity plastics. Abstract: With global oil supplies expected to deplete within the next century, novel processing techniques and material developments are becoming a necessity to ease the burden and, eventually, replace these unsustainable resources. Work has begun to replace plastics (polymers derived from crude oil) with sustainable biopolymers. Often these can be derived from waste sources or low value by-products. Poultry feathers represent one possible feedstock material for biopolymer development, however the understanding of their thermal processing and melt formation remains in its infancy. Moreover, transitioning from lab scale to industrial scale remains a significant challenge. This paper aims to carry out extrusion of feather-based polymers and further understand the method of polymer formation. A design of experiments (DOE) investigation was conducted to optimise composition and extruder set-up. Results demonstrate shearing forces, pressure and temperature were all key factors for stable feather polymer formation to occur. The investigation concluded that a feather mix (with a particle sizing of 212–500 µm) with propylene glycol, in a ratio of 70:30 respectively, processed at 125 °C represents an optimal set-up in terms of mechanical and processing properties. These outcomes develop a base-line technique for implementing feather-based polymers into the polymer industry. Characterisation (via Fourier Transform Infrared Spectroscopy and Differential Scanning Calorimetry) showed minimal changes to the thermal properties or structures of produced samples outlining potential reprocessing capability. An estimation of polymer cost generation was conducted, showing a saving of 56% compared to pure polypropylene.